Use of the game “Who am I Immunologically?” as a teaching strategy in Immunology - Ramos, César Augusto Pereira; Berbel, Emilly Moraes Berbel Moraes; Amorim, Fabiana Santos; Andrade, Heloísa; Santos, Kailane Silva; Silva, Laura Amorim; Santos, Pedro Henrique Nascimento dos; Almeida, Pedro Cerqueira; Pires, Vanessa Ribeiro; Santana, Clarissa Cunha (Research, Society and Development, 2025)
The incorporation of active and varied methodologies represents a playful and engaging strategy that enhances the learning process. The integration of games in education not only stimulates critical thinking but also cultivates analytical and argumentative skills among students. Particularly within the domain of immunology, a discipline that delves into the intricacies of the immune system, games can serve as a powerful tool to elucidate complex concepts and ignite students’ enthusiasm. This study proposes the development of a card game aimed at innovating the learning process in immunology, making it more interactive and meaningful. Consequently, the development of the educational game "Who am I immune?" was conceived as a pedagogical tool to facilitate comprehension of the immune system, with the goal of utilizing it as a means to enhance the assimilation of content taught and provide a dynamic approach to teaching the subject, rendering learning more inclusive, enjoyable, and effective. An additional benefit of this methodology is its flexibility to adapt the game’s content to meet the individual needs and experiences of students, thus enabling a contextualized and meaningful learning experience.